Complete tamponade system for management of severe postpartum vaginal haemorrhage due to uterine atony - Atilgan, Remzi (BMJ Case Rep, 2014)
A 30-year-old, 39 weeks pregnant, multiparous woman with single fetus, attended our obstetric clinic with complete cervical dilation in intractable mentum anterior presentation. The fetus was delivered by caesarean section with vertical uterine incision under general anaesthesia and lithotomy position. After surgery, examination of the vagina revealed multiple, serious tears with severe haemorrhage. Vaginal bleeding could not be controlled by sutures and concurrently uterine atony developed, which could not be controlled with medical treatment. Owing to intractable bleeding from uterus and vagina, a complete tamponade system was used. After the instillation of the uterine balloon with 500 mL and vaginal balloon with 300 mL liquid, the bleeding was controlled. The estimated blood loss was 3200 mL. The vaginal wound healed well during the postoperative 2 weeks. A complete tamponade system may be an effective treatment method for treatment of postpartum haemorrhage owing to vaginal lacerations and uterine atony.